Blue semipolar InGaN microcavity light-emitting diode with varying cavity lengths from 113 to 290 nm. (16th March 2021) - Back, Joonho; Rienzi, Vincent; Wong, Matthew S.; Li, Hongjian; DenBaars, Steven P.; Weisbuch, Claude; Nakamura, Shuji
Abstract: Blue semipolar InGaN microcavity light-emitting diodes (MC-LEDs) with geometrical cavity lengths of 113, 205 and 290 nm were fabricated, demonstrating the feasibility of ultra-thin MC-LEDs. Precise positioning of the active layer in the cavity is shown to be possible. The peak external quantum efficiencies (EQEs) of 113 nm cavity length MC-LEDs with quantum well (QW) positions at 46%, 60% and 75% of the cavity height counted from the top of the device were 0.6%, 2.5% and 0%, respectively. The 113 nm cavity MC-LED with the QW position of 75% should have the highest light extraction efficiency of 35% but showed no emission due to a high leakage current caused by the device fabrication process. The 290 nm cavity length MC-LED had the highest peak EQE of 6.7%. The peak wavelength was almost constant at 430 nm at a current density from 289 to 1868 A cm −2 under pulsed operation.